Effects of vitamins, calcium, and phosphorus in nursery pig and sow diets on bone mineralization and growth performance - Becker, Larissa Lynn (Kansas State University, 2024)
This dissertation is comprised of 5 chapters consisting of a literature review on calcium (Ca) and phosphorus (P) requirements in reproducing sows, two experiments evaluating the effects of vitamin D metabolites in nursery pig diets, two experiments evaluating over-supplementing folic acid in nursery pigs, a meta-regression analysis of narasin in grow-finish pigs, and an experiment evaluating two different farrowing systems during lactation. In chapter 1, a literature review was conducted to summarize Ca and P requirements in gestation and lactating sows derived from empirical and factorial models. The large variation among results of empirical studies and factorial models makes it difficult to define precise Ca and P requirements for gestating and lactating sows. However, with the most recent data a minimum level of 6.0 g/d of STTD P during gestation and 22.1 g/d of STTD P during lactation appear to meet basal requirements. The objective of chapter 2 was to determine the effects of added 25(OH)D₃ with three levels of STTD P on nursery pig growth performance, bone and urine characteristics, and serum vitamin D. Overall, added 25(OH)D₃ had limited effect on growth performance; however, an increase in serum concentrations of 25(OH)D₃ and 24,25(OH)₂D₃ was observed. The addition of 25(OH)D₃ to P-deficient diets increased percentage bone ash. Increasing STTD P to 100% of NRC (2012) requirement estimate increased growth and 130% of NRC maximized bone ash. The objective of chapter 3 was to determine the response to supplementation of 1,25(OH)₂D₃-glycoside (active form of vitamin D) provided from a plant extract on nursery pig growth performance, mortality, bone characteristics, and blood measurements. Overall, supplementation of 1,25(OH)₂D₃-glycoside had minimal impact on growth or serum parameters; however, increasing 1,25(OH)₂D₃-glycoside increased percentage bone ash. In chapter 4, two studies were conducted to determine the effect of folic acid on growth performance, SCFA concentrations, and serum homocysteine concentrations. Overall, the addition of folic acid resulted in reduced growth performance with the greatest negative impact being observed when pigs were fed 20 mg/kg. Folic acid supplementation altered SCFA concentrations and increased serum homocysteine. In chapter 5, a meta-regression analysis was conducted to evaluate the effects of added narasin in growing-finishing pig diets to predict growth rate, feed efficiency, and carcass yield. The models developed suggest important variables for predicting the percentage change in growth performance and carcass yield for pigs fed diets with added narasin include the narasin feeding duration, average weight, and growth performance of pigs fed diets without narasin. This meta-regression analysis provides equations to predict responses on growth performance and carcass yield. Lastly, in chapter 6, the effects of a pre-weaning socialization system during the lactation period on piglet growth and livability, pig lifetime performance, and subsequent sow performance were evaluated. Pigs raised in the conventional farrowing system had increased livability, lifetime growth performance, and carcass characteristics compared to the pre-weaning socialization system.
Keywords: Calcium; Phosphorus; Vitamins; Nursery pig; Sow